Experimental and Theoretical Study of the Ultrafast Dynamics of a Ni2Dy2‐Compound in DMF After UV/Vis Photoexcitation. Issue 5 (2nd May 2022) - Sold, Stefan; Mummaneni, Bharadwaj C.; Michenfelder, Nadine C.; Peng, Yan; Powell, Annie K.; Unterreiner, Andreas‐Neil; Lefkidis, Georgios; Hübner, Wolfgang
Abstract: Invited for this month's cover picture are the groups of Wolfgang Hübner (TU Kaiserslautern, Germany), Annie Powell (Karlsruhe Institut of Technology, Germany), and Andreas‐Neil Unterreiner (Karlsruhe Institut of Technology, Germany). The cover picture shows the Dy2 Ni2 ‐molecular magnet being excited with a UV/Vis laser pulse, together with its time‐resolved spectrum after the pulse. The comparison of the theoretical and the experimental spectra together with both the observed and the calculated relaxation times reveal, among others, three key points: the intermediate states participating in the laser‐induced dynamics, the partial metal‐to‐oxygen charge‐transfer excitations, and the order of magnitude of the coupling of the molecular magnet to the thermal bath of the environment. Read the full text of their Full Paper at 10.1002/open.202100153 . Abstract : "… The comparison of the theoretical and the experimental spectra together with both the observed and the calculated relaxation times reveals three key points …" Find out more about the story behind the front cover research at 10.1002/open.202100153 .